Nutritional status, cardiovascular health, VO2 max and habits in university students: a comparison between two health promotion careers (2017)
Introduction: University students are at a moment of their life cycle that is key for the adoption of different lifestyles.Objective: The purpose of this study was to determine and compare VO2 max, fat mass percentage, biochemical profile, and alcohol and tobacco consumption in university students of two undergraduate programs.Materials and methods: 53 first year students with an average age of 19.25 years were included in this study. 30 were enrolled in the in Physical Education Pedagogy program, and 23 in the Nutrition and Dietetics program offered by Universidad La Frontera, class of 2014. Assessment included weight, size, BMI, waist circumference, fat mass percentage, blood pressure, biochemical profile and VO2 max.Results: 32% of the students were overweight, 50.9% reported altered blood pressure, 28.3% had prehypertension, and 22.6% had high blood pressure. Furthermore, 50.9% had a fat mass level above normal, 18.8% were regular smokers, and 41.5% reported frequent alcohol use. Regarding VO2 max, 48.9% were in the poor to fair range. The comparison by program showed significant differences in the variables height, VO2 max (maximum aerobic capacity) and fat mass percentage (p0.05).Conclusions: Students are prone to develop chronic noncommunicable diseases, which is a worrying situation since they will become promoters of healthy lifestyles according to their career path.